Fixed Point Theorems for Multivalued Mappings Involving α-Function. (25th June 2014) - Ali, Muhammad Usman; Kiran, Quanita; Shahzad, Naseer
Abstract : We obtain some fixed point theorems with error estimates for multivalued mappings satisfying a newα -ψ -contractive type condition. Our theorems generalize many existing fixed point theorems, including some fixed point theorems proved forα -ψ -contractive type conditions.